2001
DOI: 10.1074/jbc.m009677200
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of p130 with, and Consequent Inhibition of, the Catalytic Subunit of Protein Phosphatase 1α

Abstract: The protein p130 was originally isolated from rat brain as an inositol 1,4,5-trisphosphate-binding protein with a domain organization similar to that of phospholipase C-␦1 but which lacks phospholipase C activity. Yeast two-hybrid screening of a human brain cDNA library for clones that encode proteins that interact with p130 has now led to the identification of the catalytic subunit of protein phosphatase 1␣ (PP1c␣) as a p130-binding protein. The association between p130 and PP1c␣ was also confirmed in vitro b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
70
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 68 publications
(76 citation statements)
references
References 25 publications
6
70
0
Order By: Relevance
“…3). PP1 caused the release of 32 P from phosphorylated SNAP-25, which was inhibited by the addition of purified recombinant PRIP-1 but not by the mutant PRIP-1, whose residue Phe-97 was replaced with Ala, lacking PP1 binding ability (29), as shown in Fig. 3A.…”
Section: Regulation Of Dephosphorylation Of Snap-25 By Prip-1-we Havementioning
confidence: 89%
See 3 more Smart Citations
“…3). PP1 caused the release of 32 P from phosphorylated SNAP-25, which was inhibited by the addition of purified recombinant PRIP-1 but not by the mutant PRIP-1, whose residue Phe-97 was replaced with Ala, lacking PP1 binding ability (29), as shown in Fig. 3A.…”
Section: Regulation Of Dephosphorylation Of Snap-25 By Prip-1-we Havementioning
confidence: 89%
“…We isolated PRIP as a novel inositol 1,4,5-trisphosphate/PtdIns(4,5)P 2 -binding protein (23,32,34,35) and later identified it also as a protein phosphatase (PP1 and PP2A)-anchoring protein (29,30). Furthermore, very recently we found that PRIP associates with Akt when it is phosphorylated to be active (31), indicating that PRIP is a unique molecule participating in phosphorylation events from both sides.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…PRIP-1 has a number of binding partners, including catalytic subunit of protein phosphatase 1␣ (PP1␣) and GABA A receptor-associated protein (GABARAP) Yoshimura et al, 2001; Kanematsu et al, 2002). A role for PRIP-1 in regulating GABA A receptor function is further suggested by the phenotype of PRIP-1 knock-out (PRIP-1 Ϫ/Ϫ ) mice, which have altered GABA A receptor pharmacology and behavior .…”
Section: Introductionmentioning
confidence: 99%